(untitled) (Global Journal of Management and Business Research, 2023)
Nigeria s balance of payment crisis has been at the heart of its frequent recession and incessant currency devaluation Hence it is imperative that major economic policies and strategies address this issue As this paper as showed if Nigeria could consistently attain overall balance of payment surplus the naira will be strengthened and the economy will flourish Therefore this paper attempts to demystify Nigeria s balance of payment deficit while offering recommendations to improve the weak balance of payment While the structural approach to adjusting balance of payment crisis seems to be the method with lasting economic change it appears the most difficult to execute